Examining Students' and Teachers' Perspectives and Practices of AI - Timur, Zulfikar Muria; Setiawan, Slamet; Mustofa, Ali; Anam, Syafi'ul (English Education: Jurnal Tadris Bahasa Inggris, 2024)
The rapid development of technology has made an earth-shattering innovation take the world by storm: Artificial Intelligence (AI). This study aims to determine the perceptions and practices of teachers and students in using AI in the classroom. Four university teachers and 30 students were sent questionnaires, and four teachers and 23 students were given online structured interviews.  The results stated that in the student group, as many as 24 respondents (80%) had a good perception of AI, and six respondents (20%) had an excellent perception of AI. Meanwhile, in the teacher group, three respondents (75.0%) had a favorable perception, and one teacher respondent (25.0%) had a very favorable perception of AI. This result is also reinforced by the practice of students' and teachers' perspectives of AI, which state that AI is beneficial in eliciting students’ responses, attracting students’ attention, and increasing their motivation and creativity. Nevertheless, AI is just an intelligent tool; no matter how excellent and optimal the tool is, how much potential humans can utilize depends on the use and the user himself.